PENINGKATAN KOMPETENSI PEDAGOGI GURU SD NEGERI TAENG MELALUI PELATIHAN MODEL-MODEL PEMBELAJARAN DI ERA PASCA PANDEMI COVID 19 - Maria Ulviani; Hilda Hafid; Akbar Avicenna (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2023)
The objectives of this research and service are (1) to improve the digital pedagogical competence of teachers at SDN Taeng in applying appropriate learning strategies; (2) to improve the ability of teachers to use learning models. In the implementation of the program, the approach method offered is a participatory approach. In collecting data on the results, the team distributed questionnaires to the teachers as participants who participated in the training to determine the level of satisfaction, compatibility, usability/acceptability of applying digital pedagogy in the learning process. One of the online interactive media used in this research and service is Google Classroom. The output of this service is expected that teachers are able to adapt to online learning media, implement digital pedagogy in online learning, especially Google Classroom so that in addition to being a means of distributing assignments, submitting assignments and assessing collected assignments, but teachers can also provide a persuasive approach to student learning development. besides that through this training teachers are able to make learning modules about interactive and innovative learning models.